2018
DOI: 10.1016/j.jid.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Reticulum-Associated Protein RTN1A Specifically Identifies Human Dendritic Cells

Abstract: RTN1 is an endoplasmic reticulum-associated protein that was initially identified in neuronal tissues. Here we show that the main isoform RTN1A is a marker for dendritic cells. In the skin, HLA-DRCD1aCD207CD11c Langerhans cells were the only cells in the epidermis, and HLA-DRCD11c dendritic cells were the main cells in the dermis, expressing this protein. RTN1A dendritic cells were also found in gingiva, trachea, tonsil, thymus, and peripheral blood. During differentiation of MUTZ-3 cells into Langerhans cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This finding suggested that also other dermal populations may have infiltrated the epidermis upon negative pressure and/or markers may have been upregulated on resident LCs. Confirming our previous observation in normal skin 34 , CD11c expression was undetectable on resident LCs in normal epidermis (Fig. 4G-J) and blister roof epidermis (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding suggested that also other dermal populations may have infiltrated the epidermis upon negative pressure and/or markers may have been upregulated on resident LCs. Confirming our previous observation in normal skin 34 , CD11c expression was undetectable on resident LCs in normal epidermis (Fig. 4G-J) and blister roof epidermis (Fig.…”
Section: Resultssupporting
confidence: 92%
“…S3E-H), CD11c ( Fig. S3M-P) and RTN1A, a recently identified marker for cells of the DC lineage 34 ( Fig. 5B; Fig.…”
Section: Resultsmentioning
confidence: 81%
“…PBMCs and neutrophils (purity >95%) were isolated as described in Gschwandtner et al and Polak et al ( 32 , 33 ), and 2 × 10 5 cells in 30 μl RPMI 1640 medium were added onto the membrane of the migration system (ChemoTx; Neuro Probe, Gaithersburg, MD, USA). The lower compartment was filled with 300 μl of 100 ng/ml CXCL8 (neutrophils) or CXCL13 (PBMCs).…”
Section: Methodsmentioning
confidence: 99%
“…Next potential markers are CD207 [66], and CD209 (DC-SIGN), which is expressed on plasmacytoid DCs (pDCs) and moDCs and is greatly expressed on DCs in mucosal tissues. The expression of this last marker is increased after LPS-mediated DC maturation induction [67].…”
Section: The Immunophenotyping Of Modcsmentioning
confidence: 99%